Therapeutic Modulation of Virus-Induced Oxidative Stress via the Nrf2-Dependent Antioxidative Pathway - Lee, Choongho (Oxid Med Cell Longev, 2018)
Virus-induced oxidative stress plays a critical role in the viral life cycle as well as the pathogenesis of viral diseases. In response to reactive oxygen species (ROS) generation by a virus, a host cell activates an antioxidative defense system for its own protection. Particularly, a nuclear factor erythroid 2p45-related factor 2 (Nrf2) pathway works in a front-line for cytoprotection and detoxification. Recently, a series of studies suggested that a group of clinically relevant viruses have the capacity for positive and negative regulations of the Nrf2 pathway. This virus-induced modulation of the host antioxidative response turned out to be a crucial determinant for the progression of several viral diseases. In this review, virus-specific examples of positive and negative modulations of the Nrf2 pathway will be summarized first. Then a number of successful genetic and pharmacological manipulations of the Nrf2 pathway for suppression of the viral replication and the pathogenesis-associated oxidative damage will be discussed later. Understanding of the interplay between virus-induced oxidative stress and antioxidative host response will aid in the discovery of potential antiviral supplements for better management of viral diseases.